Mitigasi Bencana Alam Melalui Permainan Tradisional Pada Anak Usia Dini - Ayu Fajarwati; Eka Setiawati; Yusdiana Yusdiana (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2023)
Indonesia is one of the countries prone to natural disasters. Because of this, educators must stimulate children by introducing practices related to dealing with emergencies (natural disasters). This study aims to describe natural disaster mitigation through traditional games at an early age in the Rangkasbitung sub-district, Banten. This study used the descriptive qualitative method. Descriptive research was chosen because this research is a form of research that describes existing phenomena, both natural and human-engineered. The phenomenon is then explained clearly without use based on the results of existing research. Based on the results of the study, it was found that children were able to be ready during simulations related to natural disaster mitigation, apart from being told by the teacher through listening, also direct practice in dealing with disaster situations which were carried out by raising traditional games such as